Climatic stalemate in Bangkok - Abd Razak, Dzulkifli (2009)
AS the United Nations negotiations on climate change drew to a close on Friday in Bangkok, the atmosphere of pessimism was already being widely reported by many of those involved, especially from developing countries. The prospect of an abandoned Kyoto Protocol was said to be in the air, thanks to the developed economies, as they seemed to be more eager to do away with it when it expires in a couple of years time. Firmsounding pledges made during the UN Climate Summit in New York of late to fight the climate change have not been followed through in earnest, resulting in the Chair of the Kyoto Protocol to comment: “We will be a laughing stock come December 18,” in reference to the Copenhagen Climate Conference to be held from Dec 7 to 18.